Education in crisis : a systematic review of teaching and learning in the COVID-19 era - Dhurumraj, Thasmai; Ramaila, Sam (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
The COVID-19 pandemic has profoundly disrupted education systems worldwide, necessitating a rapid shift to remote learning and exposing both challenges and opportunities within teaching and learning practices. Guided by Bandura’s Social Cognitive Theory, which emphasizes the interplay between personal, behavioural, and environmental factors in learning this systematic review aims to synthesize the existing literature on the impact of the pandemic on education, focusing on the multifaceted challenges faced by educators and students, as well as the emergent opportunities for innovation and improvement. Key challenges identified include technological disparities, diminished student engagement, and increased stress among educators and learners. Concurrently, the pandemic has catalysed advancements in educational technology, fostered greater flexibility in teaching methodologies, and highlighted the importance of social-emotional learning. A comprehensive search of multiple academic databases was conducted, followed by rigorous screening based on predefined inclusion and exclusion criteria, quality appraisal of selected studies, and thematic synthesis of findings, in alignment with PRISMA guidelines, to ensure transparency and methodological rigor. By examining these dimensions, this review provides a comprehensive understanding of the pandemic's educational implications and offers insights into strategies for enhancing resilience and effectiveness in future educational disruptions. The findings underscore the need for equitable access to technology, support for mental health, and the integration of adaptive pedagogical approaches to create a more robust and inclusive education system. These insights extend beyond the COVID-19 context, offering guidance for educational preparedness and responsiveness in future global crises.
Journal article published in the African Perspectives of Research in Teaching and Learning Journal Issue 5, Volume 9, 2025 Special Issue
Keywords: COVID-19; Learning opportunities; Remote learning; Teaching challenges; Technological disparities; Education; Distance education; Internet in education; COVID-19 Pandemic, 2020-2023; Teaching and learning